Validated Work Life Balance Scale for Bank Employees: Skala Work Life Balance Tervalidasi untuk Karyawan Bank - Amarisma Gusria; Muhammad Fadhli; Jihan Sulaiman (Psikologia : Jurnal Psikologi, 2026)
The Purpose of This study is to examine the validity and reliability of a work-life balance’s instrument among bank employees using the Confirmatory Factor Analysis (CFA) approach with SMART PLS. Work-life balance is important aspect in industrial and organizational psychology insasuch as it is associated with psychological well-being, work productivity, and quality of life for the employee. The high work demands in the banking sector make it necessary to measure work-life balance using a good quality of instruments. This research employed a quantitative approach involving 330 bank employees as research participants. The sampling technique used was purposive sampling. Data analysis was conducted through outer model testing to evaluate construct validity and reliability. Convergent validity was assessed using loading factor values and Average Variance Extracted (AVE), while reliability was evaluated through Cronbach’s alpha and Composite Reliability values. The findings indicated that 16 out of 17 items were considered valid and reliable. Furthermore, all dimensions of the work-life balance construct adequately reflected the measured construct. These results indicate that the work-life balance instrument has satisfactory psychometric properties and is appropriate for use among bank employees. Highlights • Sixteen of seventeen items met the required psychometric criteria.• One PLIW item was removed due to low loading factor.• Composite Reliability and Cronbach’s Alpha confirmed strong internal consistency. Keywords Work Life Balance; Confirmatory Factor Analysis; Validity; Reliability; Bank Employees